2011
DOI: 10.1038/gene.2011.62
|View full text |Cite
|
Sign up to set email alerts
|

The dual effect of the lupus-associated polymorphism rs10516487 on BANK1 gene expression and protein localization

Abstract: Numerous loci have been found genetically associated with complex diseases, but only in a few cases has the functional variant and the molecular mechanism behind it been identified. Recently, the association of the BANK1 gene with systemic lupus erythematosus (SLE) was described. Here, we investigated the role of the associated polymorphisms on gene function and found that SNP rs17266594 located in the branch point consensus sequence has negligible effect on splicing or gene expression. The non-synonymous SNP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…25,26 As compared with the rs10516487 C major allele, the T minor allele decreases BANK1 expression, reduces the activity of BANK1 variants with increased potential for self-association, and thereby reduces B-cell responses. 27 In several large studies, the same minor allele has been associated with decreased susceptibility to systemic sclerosis, 11,28 systemic lupus erythematosus, 25 and rheumatoid arthritis. 26 These results suggest that sclerotic GVHD shares a BANK1-mediated pathogenic mechanism with several autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25,26 As compared with the rs10516487 C major allele, the T minor allele decreases BANK1 expression, reduces the activity of BANK1 variants with increased potential for self-association, and thereby reduces B-cell responses. 27 In several large studies, the same minor allele has been associated with decreased susceptibility to systemic sclerosis, 11,28 systemic lupus erythematosus, 25 and rheumatoid arthritis. 26 These results suggest that sclerotic GVHD shares a BANK1-mediated pathogenic mechanism with several autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-matched related 374 (44) 91 (46) 283 (44) HLA-matched unrelated 326 (38) 86 (43) 240 (37) HLA-mismatched related 13 (2) 1 (1) 12 (2) HLA-mismatched unrelated 134 ( (41) 67 (34) 281 (43) #450 cGy 297 (35) 78 (39) 219 (34) .450 cGy 202 (24) 53 (27) 149 (23) Prior grade 2-4 acute GVHD, no. (%) 619 (73) 137 (69) 482 (74) CLL, chronic lymphocytic leukemia; CML, chronic myeloid leukemia; MDS, myelodysplastic syndrome; MM, multiple myeloma; MPN, myeloproliferative neoplasm.…”
Section: Characteristics Of the Study Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies there was no difference in total BANK1 levels in subjects with the risk genotype versus the non-risk genotype [5]. Further studies revealed that the rs10516487 R61 risk variant correlates with decreased splicing of exon 2 of BANK1 due to loss of a splice enhancer site, leading to the reduction of BANK1 Δ2 transcript levels relative to full-length transcripts [21]. Exon 2 encodes the region of BANK1 that is reported to interact with the IP3R, but the consequences of decreased levels of the Δ2 isoform in peripheral B cells are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…And a more recent work suggested that the kinase activity of BLK enhanced BANK1-PLCγ2 (phospholipase Cγ2) binding, further supporting the role of these 2 genes in basic B cell physiology and immune-related diseases 8 . Previous genetic studies also revealed BLK rs2736340 has an expression quantitative trait loci (eQTL) effect 9 ; and the nonsynonymous SNP rs10516487 (G>A; R61H) showed a dual nature by influencing mRNA splicing and consequently the quantity of protein, and by producing a risk variant-containing protein isoform with increased potential for multimerization 10 . However, future functional analysis focusing on combination effects of these 2 SNP are needed.…”
Section: To the Editormentioning
confidence: 99%